2021
DOI: 10.1186/s41182-021-00319-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of full childhood immunization among children aged 12–23 months in sub-Saharan Africa: a multilevel analysis using Demographic and Health Survey Data

Abstract: Background Sub-Saharan Africa is one of the highest under-five mortality and low childhood immunization region in the world. Children in Sub-Saharan Africa are 15 times more likely to die than children from high-income countries. In sub-Saharan Africa, more than half of under-five deaths are preventable through immunization. Therefore, this study aimed to identify the determinant factors of full childhood immunization among children aged 12–23 months in sub-Saharan Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 42 publications
13
55
0
1
Order By: Relevance
“…The scatter plot results show that the plots spread on the left and top side, this means that the higher the percentage of the less of midwives in primary health care, the lower complete basic immunization coverage in the province of Indonesia (Figure 2). This is in line with previous research which stated that the higher a person's income level, the higher the chance for complete basic immunization (Debie et al, 2020;Fenta et al, 2021). Immunization coverage gaps due to income-based inequality were widened by maternal education and place of residence (Sharma et al, 2021).…”
Section: Correlation Between Poor Population and Complete Basic Immunizationsupporting
confidence: 90%
“…The scatter plot results show that the plots spread on the left and top side, this means that the higher the percentage of the less of midwives in primary health care, the lower complete basic immunization coverage in the province of Indonesia (Figure 2). This is in line with previous research which stated that the higher a person's income level, the higher the chance for complete basic immunization (Debie et al, 2020;Fenta et al, 2021). Immunization coverage gaps due to income-based inequality were widened by maternal education and place of residence (Sharma et al, 2021).…”
Section: Correlation Between Poor Population and Complete Basic Immunizationsupporting
confidence: 90%
“…The role of mother's education as determinants of vaccination utilization has also been stated by other studies. [49][50][51] Adedokun et al 2020 and Khanam et al, 2020 discussed that education has positive impact on healthcare seeking of the caregivers by empowering them on decision making regardless of their social, family and child factors. 52,53 Hence the association might be justified by the fact that educated parents have more understanding of the importance of childhood vaccination and child health than uneducated parents.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who have more frequent contact with health professionals seem to be more aware of their children's health as they receive more information about immunization and child health. A study conducted by [4,14,15,17] confirmed this truth.…”
Section: Discussionmentioning
confidence: 74%
“…More than half of these deaths have occurred in sub-Saharan Africa. Three of the five countries (Ethiopia, Nigeria, and the Democratic Republic of Congo) in which half of the world's child deaths have occurred are in sub-Saharan Africa [4].…”
Section: Introductionmentioning
confidence: 99%